GEOLOGI DAN ANALISIS JENIS BATUAN ASAL PADA PEMBENTUKAN ENDAPAN NIKEL LATERIT DI KECAMATAN BUNTA, KABUPATEN BANGGAI - Yuriadi, Bilal Aditya; Arifin, Yayu Indriati; Hutagalung, Ronal (UNM Geographic Journal, 2024)
This research is motivated by the presence of nickel laterite deposit potential originating from various types of lithology in the Bunta sub-district, Banggai Regency, which needs to be followed up to facilitate exploration of nickel laterite. The research area is located at coordinates 122°15'8" - 122°15'18" South Latitude and 0°50'36" - 0°51'18" East Longitude, covering an area of approximately ±441 hectares. The purpose of this study is to understand the geology of the research area and the types of source rocks that have formed nickel laterite deposits in the area. The data used in this research includes geomorphological data, structural data, lithological data, and rock samples. The collected data will produce information on rock types and interpretations of the geological history of the research area. Based on the analysis, the geomorphology of the research area consists of three units: structural hills, denudational hills, and interhill plains. The rock types in the research area include lherzolitic serpentinized rocks and serpentinites, which are part of the ultramafic complex. The observed and developed structure in this area is tensile fractures with a dominant direction of Northwest - Southeast. The results show that this area could be exposed due to oceanic crust subduction, which has uplifted ultramafic rocks to the surface, leading to physical and chemical weathering and the formation of nickel laterite deposits.